Position and Differentiation of Firms in Technology Space - Arts, Sam; Cassiman, Bruno; Hou, Jianan (Management Science, 2023)
Although the rate of invention by firms and the effect on firm performance have been central themes in economics and strategy, the position and differentiation of invention by firms have received less attention. We develop a method to characterize a firm’s technology portfolio based on the semantic content of patents that allows us to map a firm’s unique spatial position relative to every other firm in technology space and to measure the overall differentiation of a firm’s technology portfolio. Using a large panel of U.S. public firms from 1980 to 2015, we illustrate that technology differentiation has a strong positive correlation with firm performance, particularly in research and development-intensive industries and industries with strong product market rivalry. We also show that technology differentiation is associated with subsequent differentiation from competitors in the product market and a reduction in outgoing technology spillovers to other firms. We provide open access to code and data to characterize the technology portfolio of firms and to measure the technological position and differentiation of U.S. public firms. This paper was accepted by Alfonso Gambardella, business strategy. Funding: S. Arts acknowledges support from KU Leuven [Grant 3H200208] and National Bank Belgium [Grant 3H160338]. B. Cassiman acknowledges support from Fonds Wetenschappelijk Onderzoek - Vlaanderen [Grant G071417N]. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2023.00282 .